Human Capital Accumulation and Public Sector Growth - Tanzi, Vito.; Zee, Howell (Washington, D.C. : International Monetary Fund, 1995)
The present paper takes a fresh theoretical and empirical look into the relationship between Wagner's law and economic development. It introduces human capital into a classic two-sector model of unbalanced growth. It shows that, as an economy develops, changes in the relative returns to human capital and unskilled labor, as a result of changes to their relative scarcities, could have a significant impact on the size of the government sector, depending in part also on the difference in relative factor intensities between outputs of the private and government sectors. This conjecture is broadly supported by empirical evidence based on a cross-section analysis of a large sample of developed and developing countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet